Analysis of Heavy Metal Pb in Blood Cockle in Lembar Waters, West Lombok - Thoy Batun Citra Rahmadani; Zaenal Abidin; Wastu Ayu Diamahesa; Damai Diniariwisan; Alis Mukhlis (Jurnal Sains dan Teknologi Perikanan, 2026)
Heavy metal present in marine water can affect aquatic organisms, particularly bivalves that function as filter feeders and therefore have a high potential to accumulate heavy metals in their bodies. Blood cockle (Anadara granosa) is one of the marine organisms commonly found in the waters of West Lombok, especially in the Lembar area, which is influenced by port activities and coastal community activities. This study aimed to analyze the concentration of lead (Pb) in blood cockles and sediments in the waters around Lembar, West Lombok, and to determine the safe consumption limit of cockles for the community. Samples of blood cockles and sediments were collected from three observation stations in Lembar waters. Each sample was collected in triplicate as replicates. The Pb concentration was analyzed using Atomic Absorption Spectrophotometry (AAS) methods and the results were compared with applicable quality standards. The results showed that the Pb concentration in blood cockles ranged from 0.043–0.051 mg/kg with an average value of 0.047 mg/kg. These values are below the maximum limit set by the government, which is 0.1 mg/kg. Meanwhile, Pb concentrations in sediments ranged from 0.887–1.32 mg/kg and were still below the sediment quality standard of 25 mg/kg. The calculation of the safe consumption limit indicated that the Maximum Tolerable Intake (MTI) of blood cockles ranged from 29-35 kg/week for adults with an average body weight of 60 kg, indicating that blood cockles from the Lembar waters are still safe for consumption.